The society of nematologists at 50, and where to from here? - Webster, John M (Journal of nematology, 2012)
Nathan Cobb, as the father figure of the Society of Nematologists, set an example to later generations of nematologists in his studies of nematode biology. In the 50 years of the Society's existence nematological research has greatly expanded that knowledge base. Opportunities over the next 50 years are boundless in view of advancing technologies and emerging challenges, and this leads to speculation as to what future nematological research advances will enhance peoples' quality of life